Usinabilidade do aço inoxidável supermartensítico durante o serramento circular utilizando serras com insertos intercambiáveis de metal duro revestidos e sem revestimento - Maria Cristina Moreira (2016)
Supermartensitic stainless steel is the most suitable material for the manufacture of rigid tubes for oil and natural gas extraction from the Pre-Salt layer because it possesses superior mechanical properties in aggressive environments. Therefore, the demand increase for this product has required the improvement of the production process. Consequently, it is necessary the better understanding of the phenomena occurring during machining of this material, especially the study of circular sawing. The work aims to identify the main factors affecting the machinability of supermartensitic stainless steel when circular sawing using uncoated and coated (by means of PVD and MT-CVD techniques) indexable tungsten carbide inserts. More specifically, the influence of the input parameters (cutting speed, feed rate and insert coating) on the output parameters (cutting force, temperature, surface quality and chip) is investigated using analysis of variance with a confidence interval of 95%. In addition to that, tool wear and subsurface alterations induced by circular sawing on the work material were assessed. The results indicated that cutting force was reduced as cutting speed was elevated and increased with feed rate for the three saw blades. Cutting temperature increased with cutting speed and feed rate and the highest value was observed when cutting with uncoated inserts. The lowest inserts wear was observed with MT-CVD inserts coted. As far as the integrity of the machined surface is concerned, the slot width analysis indicated that the cutting parameters did not affect its value. Slot roughness increased with cutting parameters when the MT-CVD coated inserts were used. Burr higher increased with cutting speed only when uncoated inserts were tested and the opposite behavior was noted when feed rate was elevated. The microstructure and microhardness of the work material did not change with the increase of cutting speed for the three saw blades. Short and segmented chip were produced, however, when cutting speed was elevated connected chips were generated.